Energy Valorization of Marine Algae of the Type Ulva sp. Through the Manufacture of Combustible Briquettes - Ba, Kalidou; Faye, Mamadou; Toure, Alpha Ousmane (European Scientific Journal, ESJ, 2026)
Algae briquettes today represent a major international challenge in terms of reducing greenhouse gases and the energy transition. They offer a sustainable and renewable alternative to global dependence on fossil fuels. This study aims to valorize macroalgae of the genus Ulva sp., recovered from the pier of the C3 power plant of SENELEC in Dakar, Senegal, into combustible briquettes intended to play a similar role as charcoal and butane gas for cooking. The production method consists of mixing a constant mass of algae powder with a varying percentage (20% to 50%) of a mineral binder obtained from fluosilicic acid, a waste product from Senegalese chemical industries. The formulation yielded four briquette models: BAL50, BAL40, BAL30, and BAL20. Physicochemical analyses as well as combustion evaluations were carried out to assess the quality of the combustible briquettes. The results obtained showed that BAL20 have a lower heating value (LHV) of 2254 Kcal/Kg and a consumption time of 85 min, superior to BAL50, BAL40, and BAL30. Analysis of variance showed that the effect of ash content is highly significant (p = 0.0307 < 5%), indicating a clear influence of ash content on LHV.